Bredigite-Magnetite (Ca7MgSi4O16-Fe3O4) nanoparticles: A study on their magnetic properties - Khandan, Amirsalar; Ozada, Neriman (Elsevier Science Sa, 2017)
The aim of this study is to evaluate the hyperthermia application of a novel bredigite-magnetite nano-composite for bone tissue engineering. Magnetite nanoparticles were synthesized by the co-precipitation method and then composited with bredigite powders via a mechanical milling route and subsequent sintering process. Bredigite-Magnetite nanocomposite possessed a homogeneous dispersion of magnetite nanoparticles, which was confirmed by the absence of large aggregates. To evaluate the heat release of the composite nanoparticles, an alternating magnetic (AC) field was applied. The results showed an increase in the temperature, as a result of the increasing magnetite concentration. The sample containing 30 wt.% magnetite particles showed a temperature increase about 27 degrees C during 50 s. Generally, the present work confirmed that the bredigite-magnetite nanocomposite can be considered as an assuring candidate in hyperthermia applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Ceramic; Nanocomposite; Magnetic properties; Scaffold